2019
DOI: 10.1088/1742-6596/1402/3/033058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cage density on the quality of broiler chicken meat

Abstract: One of the maintenance management of Broilers is the regulation of cage density. In the tropics, cage density affects comfort in a cage, high temperature and humidity are the main causes of stress in chickens. Cages with in apropriate densities have a negative impact on meat production and quality performance. The study aims to identify cage density to the quality of broiler chicken meat. The study used a completely randomized design with 3 treatments, namely density 8, 10 and 12 tails per square meter, each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Poultry experiencing heat stress will release excess heat to maintain stability due to heat stress [17]. Research by Mardewi et al [19] indicated that the higher the density level, the higher the ambient temperature in the cage. The increase in environmental temperature is one factor in the increase in the body temperature of livestock.…”
Section: Body Temperature Measurementsmentioning
confidence: 99%
“…Poultry experiencing heat stress will release excess heat to maintain stability due to heat stress [17]. Research by Mardewi et al [19] indicated that the higher the density level, the higher the ambient temperature in the cage. The increase in environmental temperature is one factor in the increase in the body temperature of livestock.…”
Section: Body Temperature Measurementsmentioning
confidence: 99%